Analisis Peran Klausula Baku Perjanjian Kredit Pinjaman Online Dalam Menangkal Penyalahgunaan Dana oleh Debitur: Studi Yuridis Terhadap Kasus Penggunaan Dana Kredit Untuk Judi Online - Wildan, Ahmad; Hayat, Gian Muzakir; Akbar, Muhammad Rayhan Fasya; Daniel, Theodore (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The advancement of information technology has triggered the emergence of fintech-based online loan services, providing easier access to financing for the public. While offering convenience, these services also raise legal issues, particularly concerning the misuse of loan funds for illegal activities such as online gambling. This study aims to evaluate the extent to which standard clauses in online loan agreements are effective in preventing the misuse of funds by borrowers, and to examine this from the perspective of contract law. The findings indicate that standard clauses are generally unilaterally drafted by the service providers without explicitly prohibiting the use of funds for unlawful activities. This situation leads to weak control over fund usage and limited legal accountability. From a contract law perspective, such misuse can be considered a violation of the agreement's purpose and the principle of good faith, potentially resulting in a breach of contract.